Ibogaine/Noribogaine in the Treatment of Substance Use Disorders: A Systematic Review of the Current Literature - Mosca, Alessio; Chiappini, Stefania; Miuli, Andrea; Mancusi, Gianluca; Santovito, Maria C.; Di Carlo, Francesco; Pettorruso, Mauro; Corkery, John M.; Canessa, Carlos; Martinotti, Giovanni; Di Giannantonio, Massimo (Current Neuropharmacology, 2023)
Background: Ibogaine and noribogaine are psychedelic substances with dissociative properties naturally occurring in plants of the Apocynaceae family. Research has shown their efficacy in treating substance use disorders (SUD), particularly in opiate detoxification, but their efficacy and toxicity are still unclear. Objective: This review aims to assess the anti-addictive role of ibogaine and evaluate its side effects. Methods: A systematic literature review was conducted on the 29th of November 2021 using PubMed, Scopus and Web of Science databases through the following search strategy: (
Keywords: addiction